Investigation of the DNA Damage and Oxidative Effect Induced by Venlafaxine in Mouse Brain and Liver Cells - Eduardo Madrigal-Bujaidar; Rogelio Paniagua-Pérez; Michael Joshue Rendón-Barrón; José Antonio Morales-González; Eduardo O. Madrigal-Santillán; Isela Álvarez-González (Toxics, 2022)
Venlafaxine is an antidepressant used worldwide. Therefore, studies to confirm its safe use are mandatory. This report evaluated the drug DNA damage capacity in the brain and liver of ICR mice, and its oxidative effect on DNA, lipids, and proteins, as well as the amount of nitrites, also in the brain and liver. Determinations were made at 2, 6, 12, and 24 h post-treatment, excluding DNA oxidation that was observed at 2 h. The tested doses of venlafaxine were 5, 50, and 250 mg/kg. The results showed DNA damage in the brain with the two more elevated doses of venlafaxine at 2 and 6 h post-treatment and also at 12 h in the liver. The comet assay plus the FPG enzyme showed DNA damage in both organs with all doses. The two high doses increased lipoperoxidation in the two tissues from 6 to 12 h post-administration. Protein oxidation increased with the three doses, mainly from 2 to 12 h, and nitrite content was elevated only with the high dose in the liver. The drug was found to affect both tissues, although it was more pronounced in the liver. Interestingly, DNA oxidative damage was observed even with a dose that corresponds to the therapeutic range. The clinical relevance of these findings awaits further investigations.